Overriding plate structure of the Nicaragua convergent margin: Relationship to the seismogenic zone of the 1992 tsunami earthquake. (3rd September 2013) - Sallarès, Valentí; Meléndez, Adrià; Prada, Manuel; Ranero, César R.; McIntosh, Kirk; Grevemeyer, Ingo
<x xml:space="preserve">Abstract</x> [1] We present 2‐D seismic velocity models and coincident multichannel seismic reflection images of the overriding plate and the inter‐plate boundary of the Nicaragua convergent margin along two wide‐angle seismic profiles parallel and normal to the trench acquired in the rupture area of the 1992 tsunami earthquake. The trench‐perpendicular profile runs over a seamount subducting under the margin slope, at the location where seismological observations predict large coseismic slip. Along this profile, the igneous basement shows increasing velocity both with depth and away from the trench, reflecting a progressive decrease in upper‐plate rock degree of fracturing. Upper mantle‐like velocities are obtained at ∼10 km depth beneath the fore‐arc Sandino basin, indicating a shallow mantle wedge. A mismatch of the inter‐plate reflector in the velocity models and along coincident multichannel seismic profiles under the slope is best explained by ∼15% velocity anisotropy, probably caused by subvertical open fractures that may be related to fluid paths feeding known seafloor seepage sites. The presence of a shallow, partially serpentinized mantle wedge, and the fracture‐related anisotropy are supported by gravity analysis of velocity‐derived density models. The downdip limit of inter‐plate seismicity occurs near the tip of the inferred mantle wedge, suggesting that seismicity could be controlled by the presence of serpentinite group minerals at the fault gouge. Near the trench, the inferred local increase of normal stress produced by the subducting seamount in the plate boundary may have made this fault segment unstable during earthquake rupture, which could explain its tsunamigenic character.